2016
DOI: 10.1093/cvr/cvw069
|View full text |Cite
|
Sign up to set email alerts
|

Acute heart failure with cardiomyocyte atrophy induced in adult mice by ablation of cardiac myosin light chain kinase

Abstract: Our results, using a new mouse model mimicking an acute reduction of cMLCK, suggest that cMLCK plays a pivotal role in the transition from compensated to decompensated hypertrophy via sarcomeric disorganization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 47 publications
2
56
0
Order By: Relevance
“…CaM, a known transducer of Ca 2+ signal, activates CaMKII45 to directly phosphorylate cMyBP‐C, which is a thick filament protein with physiological significance for normal myocardial contractility and stability and serves as a convergent node for signalling processes in the cardiomyocyte 46, 47. Activation of cMLCK, also regulated by CaM, appears to be pivotal to maintain the phosphorylation of MLC2v, which functions as an essential component of thick myofilament assembly and plays a critical role in maintaining normal myocardial contractility and function 48, 49. The dephosphorylation of both MLC2v and cMyBP‐C is associated with a declined cardiac function in failing human hearts and animal models of HF 46, 48.…”
Section: Discussionmentioning
confidence: 99%
“…CaM, a known transducer of Ca 2+ signal, activates CaMKII45 to directly phosphorylate cMyBP‐C, which is a thick filament protein with physiological significance for normal myocardial contractility and stability and serves as a convergent node for signalling processes in the cardiomyocyte 46, 47. Activation of cMLCK, also regulated by CaM, appears to be pivotal to maintain the phosphorylation of MLC2v, which functions as an essential component of thick myofilament assembly and plays a critical role in maintaining normal myocardial contractility and function 48, 49. The dephosphorylation of both MLC2v and cMyBP‐C is associated with a declined cardiac function in failing human hearts and animal models of HF 46, 48.…”
Section: Discussionmentioning
confidence: 99%
“…Floxed-Mylk3 homozygous mice ( Mylk3 flox ∕ flox ) (Massengill et al, 2016) were bred with transgenic mice carrying the Cre-ER ™ gene under CMV promoter, Tg(CAGGS-Cre-ER ™ ) (Hayashi and McMahon, 2002). Subsequent matings between offspring generated Mylk3 flox ∕ flox / Tg-CAGGS-Cre-ER ™, Mylk3 wild ∕ wild /Tg-CAGGS-Cre-ER ™, and Mylk3 flox ∕ flox on a mixed genetic background, mainly C57BL/6J.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were anesthetized with 1.5–2% isoflurane for M-mode ultrasound imaging of the left ventricles using Vevo700 as described previously (Briggs et al, 2008; Takeda et al, 2009; Warren et al, 2012; Massengill et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This adverse effect on heart function was attenuated by cMLCK overexpression in the absence of increased loading. Similarly, Massengill et al (2016) reported that an acute, inducible reduction of cMLCK leads to sarcomeric disorganization, fibrosis, reduced contractility and cell death, and causes severe systolic and diastolic dysfunction and rapid progression to heart failure with reduction of fractional shortening. In addition, Mylk3-KO mouse hearts, lacking expression of cMLCK, displayed a significant reduction in Ca 2+ amplitude and Ca 2+ decay rates as well as SERCA2a mRNA, implying impaired calcium handling (Massengill et al 2016).…”
Section: Introductionmentioning
confidence: 94%